2016
DOI: 10.1016/j.jsp.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of early grade retention: Effect modification by prior achievement and age

Abstract: This study examines the effects of early grade retention and different effects according to prior achievement and age. Within a population of children at risk of early retention, we compared the development throughout primary school in mathematics achievement after kindergarten retention, first-grade retention, and continuous promotion. Analyzing data from a large-scale longitudinal study using covariate balancing propensity score weighting, the findings revealed that early grade repeaters would score higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…Further, children with a learning difficulty, such as dyslexia or attention problems, can be disadvantaged for listening skills because they often suffer from difficulties with lower working memory, more limited vocabulary, and certain aspects of comprehension, such as making inferences (Jeffries & Everatt, 2004;McInnes, Humphries, Hogg-Johnson, & Tannock, 2003). With regard to grade retention, research indicates that retained students are often disadvantaged, as the learning gain for language development has already disappeared at the end of the next grade (Huddleston, 2014;Vandecandelaere, Vansteelandt, De Fraine, & Van Damme, 2016). Finally, indicators of family background such as the educational level of the parents have been directly associated with language skills and must be included as control variables in the model.…”
Section: Identifying Student-level Correlates Of Listening Skillsmentioning
confidence: 99%
“…Further, children with a learning difficulty, such as dyslexia or attention problems, can be disadvantaged for listening skills because they often suffer from difficulties with lower working memory, more limited vocabulary, and certain aspects of comprehension, such as making inferences (Jeffries & Everatt, 2004;McInnes, Humphries, Hogg-Johnson, & Tannock, 2003). With regard to grade retention, research indicates that retained students are often disadvantaged, as the learning gain for language development has already disappeared at the end of the next grade (Huddleston, 2014;Vandecandelaere, Vansteelandt, De Fraine, & Van Damme, 2016). Finally, indicators of family background such as the educational level of the parents have been directly associated with language skills and must be included as control variables in the model.…”
Section: Identifying Student-level Correlates Of Listening Skillsmentioning
confidence: 99%
“…Also, a few recent studies reported negative effects (e.g. studies based on the dataset that we will reanalyze in this article: Goos, Van Damme, Onghena, Petry, & de Bilde, 2013;Vandecandelaere, Vansteelandt, De Fraine, & Van Damme, 2016a;Vandecandelaere, Vansteelandt, De Fraine, & Van Damme, 2016b; see also: Hughes, Cao, West, Smith, & Cerda, 2017;Hughes, West, Kim, & Bauer, 2018)). However, Allen et al (2009) concluded in their meta-analysis that the negative effects in many studies may have been the result of insufficient control of selection-bias.…”
Section: Grade Retention In Primary Schoolmentioning
confidence: 99%
“…28) 2 . Como señala Choi (2017) la repetición de curso no es la única herramienta para mejorar el rendimiento de un alumno y es una medida de política educativa controvertida por cuanto los argumentos a favor de la repetición (necesidad de alcanzar un mínimo de conocimientos, falta de maduración del alumnado y medida de disuasión para favorecer el esfuerzo) por la mejora de resultados educativos (Allen, Chen, Willson, & Hughes, 2009) cuando se realiza a temprana edad (Lorence, 2009) tropiezan con las evidencias de que hay más perjuicios que beneficios en la adopción de la repetición como medida terapéutica por la incerteza de la mejora de rendimientos, la desmotivación del alumnado y su desenganche escolar (Cordero, Manchón, & Simancas, 2014;Cordero, Crespo, & Santín, 2010;Calero, Choi, & Waisgrais, 2010;Ehmke, Drechsel, & Carstensen, 2010;Reschly, & Christenson, 2013;Choi, Gil, Mediavilla, & Valbuena, 2018) que termina aceptándose y generalizándose como un mal derivado de los centros educativos agrupados por edades estándar (Vandecandelaere, Vansteelandt, De Fraine, & Van Damme, 2015) y que afecta al logro educativo posterior (Fruehwirth, Navarro, & Takahashi, 2016;Van Damme, 2015). Algunos autores recalcan la inexistencia de evidencias empíricas que justifiquen la retención del alumnado porque lo que señalan es justo lo contrario, que la retención genera impactos negativos en los comportamientos del alumnado con la escuela, en el rendimiento académico posterior (García-Pérez, Hidalgo-Hidalgo, & Robles-Zurita, 2014) y en su autoconcepto, además de un gasto económico educativo adicional (Klapproth, Schaltz, Brunner, Kellerm, Fischbach, Ugen, & Martin, 2016).…”
Section: Antecedentesunclassified